ANALISIS KONTRIBUSI RETRIBUSI PASAR TERHADAP RETRIBUSI DAERAH KABUPATEN SUMBAWA BARAT - Subhan Purwadinata; I Ismawati; E Eriani (Pusat Riset dan Publikasi, 2022)
One sources of regional revenue that was considered very important and contributed greatly to the region was the Regional Retribution. This study aims to know the contribution of market retribution toward regional retribution of Sumbawa Barat District in 2015-2019. The variables in this study consisted of the independent variable, namely the contribution of market retribution (X) and the dependent variable, namely regional retribution (Y). The population in this study were the number of shop houses, the number of stall, daily tickets and toilet. The sample used was saturated sampling technique, in which all members of the population were used as research samples. Data collection was obtained through literature study and documentation which were analyzed using the contribution equation formula. The results of study showed that the revenue of market retribution in Sumbawa Barat District was fluctuated every year. The fluctuation was caused by decreasing and increasing in revenue from market retribution and decreasing and increasing realization of regional retribution revenue. The contribution of market retribution toward regional retribution in 2015 was of 4,12%, in 2016 was 4,5%, in 2017 it was 2.60%, in 2018 it was 5.62% and in 2019 it was 8.57%.